2015
DOI: 10.5852/ejt.2015.151
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of Bradepyris Kieffer, 1905 (Hymenoptera, Bethylidae, Mesitiinae)

Abstract: Abstract. Two new junior synonyms, Pseudomesitius Duchaussoy, 1916 syn. nov. and Triglenus Marshall, 1905 syn. nov., for the genus Bradepyris Kieffer, 1905 are proposed and a new diagnosis for the genus is given. Two new species (based on males) from the Saharo-Arabian region are here described: Bradepyris jordanicus, sp. nov. and B. baleariensis, sp. nov. A brief revision, with a key to the males and females of all species of this genus, and the first male genitalia descriptions are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 527 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Argaman (2003) described Triglenusini based on the characters shared by Bradepyris Kieffer, 1905, Pseudomesitius (Duchaussoy, 1916[1914, and Triglenus Marshall, 1905. The two latter genera were treated as junior synonyms of Bradepyris by Barbosa & Azevedo (2015), and our analysis showed that Triglenusini is a paraphyletic grouping. The Mesitiini were described based on the characters shared by Anaylax Móczár, 1970a, Clytrovorus Nagy, 1972, Incertosulcus Móczár, 1970aa, Itapayos, Mesitius Spinola, 1853, Metrionotus Móczár, 1970aand Parvoculus Móczár, 1970d, and were recovered as polyphyletic in our analysis.…”
Section: Phylogenetic Inferencementioning
confidence: 84%
“…Argaman (2003) described Triglenusini based on the characters shared by Bradepyris Kieffer, 1905, Pseudomesitius (Duchaussoy, 1916[1914, and Triglenus Marshall, 1905. The two latter genera were treated as junior synonyms of Bradepyris by Barbosa & Azevedo (2015), and our analysis showed that Triglenusini is a paraphyletic grouping. The Mesitiini were described based on the characters shared by Anaylax Móczár, 1970a, Clytrovorus Nagy, 1972, Incertosulcus Móczár, 1970aa, Itapayos, Mesitius Spinola, 1853, Metrionotus Móczár, 1970aand Parvoculus Móczár, 1970d, and were recovered as polyphyletic in our analysis.…”
Section: Phylogenetic Inferencementioning
confidence: 84%